2011
DOI: 10.1534/genetics.110.119628
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Mis12 Complex Acts as a Single Functional Unit Essential for Anaphase Chromosome Movement and a Robust Spindle Assembly Checkpoint

Abstract: The kinetochore is a dynamic multiprotein complex assembled at the centromere in mitosis. Exactly how the structure of the kinetochore changes during mitosis and how its individual components contribute to chromosome segregation is largely unknown. Here we have focused on the contribution of the Mis12 complex to kinetochore assembly and function throughout mitosis in Drosophila. We show that despite the sequential kinetochore recruitment of Mis12 complex subunits Mis12 and Nsl1, the complex acts as a single fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 58 publications
3
40
0
Order By: Relevance
“…The indication of a similar change in organization between interphase and mitosis is seen for the human Mis12 protein, which shows highly dynamic association with the centromere in interphase but is stably associated with the mitotic kinetochore [9,35]. However, whereas in human cells Nsl1 is associated with interphase centromeres, where it can interact with HP1, we could neither see Nsl1 in the Drosophila interphase centromere [16,18] nor could we detect its direct interaction with HP1 (results from unpublished in vitro interaction assay experiments). This perhaps is not surprising, because Drosophila HP1 does not contain the C-terminal extension, which was shown to be responsible for the interaction between human Nsl1 and HP1 [4,36].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The indication of a similar change in organization between interphase and mitosis is seen for the human Mis12 protein, which shows highly dynamic association with the centromere in interphase but is stably associated with the mitotic kinetochore [9,35]. However, whereas in human cells Nsl1 is associated with interphase centromeres, where it can interact with HP1, we could neither see Nsl1 in the Drosophila interphase centromere [16,18] nor could we detect its direct interaction with HP1 (results from unpublished in vitro interaction assay experiments). This perhaps is not surprising, because Drosophila HP1 does not contain the C-terminal extension, which was shown to be responsible for the interaction between human Nsl1 and HP1 [4,36].…”
Section: Discussionmentioning
confidence: 86%
“…UASp-Mis12::EGFP , UASp-Nsl1::EGFP and UASp-Nuf2::EGFP lines used in this study were previously published [18]. To express fusion proteins in the early embryo, we used the α - tubulin 4 – GAL4–VP16 driver [41].…”
Section: Methodsmentioning
confidence: 99%
“…The connection of the Ndc80 complex and the KNL1 complex (KNL1 and ZW10 interacting kinetochore protein [ZWINT] in humans) to the inner kinetochore appears to differ between different cell types. The results suggest that the Mis12 complex is necessary for the localization of Ndc80 complex [Scharfenberger et al, 2003;Cheeseman et al, 2004;Kline et al, 2006;Przewloka et al, 2007Przewloka et al, , 2011Venkei et al, 2011]. However, it has been reported that kinetochore localization of Ndc80 in humans, budding and fission yeast, does not depend on KNL1 [Kiyomitsu et al, 2007;Liu et al, 2010].…”
Section: Introductionmentioning
confidence: 82%
“…When the Mis12 complex is absent, defects in chromosome alignment, biorientation, unstable kinetochore-microtubule interactions, and abnormal chromosome segregation occur [Goshima et al, 2003;Obuse et al, 2004;Kline et al, 2006;Przewloka et al, 2007;Venkei et al, 2011]. When the Mis12 complex is absent, defects in chromosome alignment, biorientation, unstable kinetochore-microtubule interactions, and abnormal chromosome segregation occur [Goshima et al, 2003;Obuse et al, 2004;Kline et al, 2006;Przewloka et al, 2007;Venkei et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…13 This notion is based on observations that depletion of CENP-E (which mediates precise interactions between kinetochores and microtubules of the mitotic spindle 14 ) or Nsl1 (which targets Bub3 to the kinetochore 15 ) induces CIN but does not cause hyperproliferation. 13 The authors suggest a SAC-independent tumor suppressor role of Bub3, on the basis Depletion of spindle assembly checkpoint (SAC) genes in Drosophila epithelial tissues leads to JNK-dependent programmed cell death and additional blockade of the apoptotic program drives tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%